2013
DOI: 10.1590/0074-0276108052013022
|View full text |Cite
|
Sign up to set email alerts
|

Prozone effects in microscopic agglutination tests for leptospirosis in the sera of mice infected with the pathogenic Leptospira interrogans serovar Canicola

Abstract: Mice experimentally infected with a pathogenic strain of Leptospira interrogans serovar Canicola produced false negative results (prozone effect) in a microscopic agglutination test (MAT). This prozone effect occurred in several serum samples collected at different post-infection times, but it was more prominent in samples collected from seven-42 days post-infection and for 1:50 and 1:100 sample dilutions. This phenomenon was correlated with increased antibody titres in the early post-infection phase. While pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some previous studies also reported similar phenomena (prozone effect) due to antibody excess in the agglutination test. 23 This is because excessive antibodies might bind to all the antigens and block all the epitope sites, while limited antibodies are able to bind more than one antigenic particle (pathogen) simultaneously and cause cross-linking. Thus, no subsequent agglutination reaction occurs in the excess of antibodies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Some previous studies also reported similar phenomena (prozone effect) due to antibody excess in the agglutination test. 23 This is because excessive antibodies might bind to all the antigens and block all the epitope sites, while limited antibodies are able to bind more than one antigenic particle (pathogen) simultaneously and cause cross-linking. Thus, no subsequent agglutination reaction occurs in the excess of antibodies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Screening by MAT is done by using one dilution instead of a dilution series as described in Basic Protocol 1. Please be aware that reactive serum samples can be missed due to the prozone effect that might occur, notably when high concentrations of anti-Leptospira antibodies are present in the test sample (Shimabukuro et al, 2013).…”
Section: Microscopic Agglutination Test Screening Indirect Readingmentioning
confidence: 99%
“…Both are transmitted mainly through the sexual route and affect populations with similar characteristics. HIV can be transported by secretions and transferred by genital ulcers[22] [23]. Serological tests for HIV have been requested in the patient in question, since complete screening is essential in individuals infected with any sexually transmitted disease, especially when it is known that an infection is a door to others, since they have the same means of dissemination.The diagnosis of syphilis is simple, depends on a good anamnesis, with em-phasis on sexual history and analysis of the lesion material to identify the treponema and/or serological tests.…”
mentioning
confidence: 99%